A Study on Consumer Satisfaction with Respect to Samsung Gadgets - Ganatra, Varsha; Aryani, Dwi Nita; binti Abd. Rahman, Nur Insyirah; Kee, Daisy Mui Hung; binti Fadzil, Nur Farra Diana; binti Hassan, Nur Iffah Atirah; binti Esa, Nur Khadijah; Mamtani, Meghna (AIBPM Publisher, 2022)
This study investigates the level of customer satisfaction with the use of Samsung gadgets, the aspects of Samsung gadgets that are most satisfying, and the differences in customer satisfaction levels based on demographics. The data for this research was obtained from 134 respondents by primary study through a questionnaire survey made for Samsung consumers to know the level of consumer satisfaction on the use of Samsung gadgets. The data were then gathered, reviewed, and classified according to the research questions and objectives stated. Tables were used to present quantitative data whereas qualitative data were present narratively. These findings indicate that the aspect that most consumers are satisfied with is the Samsung gadgets' quality.